Asuhan Keperawatan Pada Nn.P Dengan Post Operasi Appendiktomi Di Ruang Cempaka III RSUD Pandan Arang Boyolali - RUSTAM, DESY BANANI, Arina Maliya, S.Kep., M.Si.Med (2015)
Background: Appendik is a small lobe that resemble fingers attached to the cecum below the ileocecal valve, due to the emptying of the contents in the appendix to the colon ineffective and size rather small. Aim of Research: To determine the nursing care in patients with postoperative appendectomy include assessment, intervention, implementation and evaluation of nursing. Results: Diagnosis is emerging in the case of pain, risk of infection, nutritional changes less than kebutuan body. After nursing actions during 3x24 hours in getting the results already reduced pain in patients, nafsumakan increased and there is no risk of infection. Conclusion: The nursing actions will be undertaken in patients is to provide analgesic therapy and relaxation (deep breathing) can reduce pain, provide appropriate dietary therapy program can increase appetite and by keeping personal hygine risk of infection in patients not occur. Keywords: Appendicsitis, post appendectomy.